Marine and nonmarine deposition in a long-term low-accommodation setting: An example from the middle Pleistocene Qm2 unit, eastern central Italy. (April 2016) - Di Celma, Claudio; Ragaini, Luca; Caffau, Mauro
Abstract: Facies anatomy and large-scale stratigraphic organization of mid-Pleistocene strata (Qm2 Unit) exposed near the town of Ortona, eastern central Italy, have been defined through an integrated outcrop and subsurface dataset, and record sedimentation within a long-term low-accommodation setting. The studied interval can be subdivided into nine facies associations, reflecting a range of continental, marginal marine, nearshore and innermost shelf environments, and contains a well-preserved record of high-frequency relative sea-level changes in the form of a stack of three unconformity-bounded sequences. Each of the three sequences, designated Qm23, Qm22, and Qm21 from oldest to youngest, consists of a specific subset of the nine identified facies associations as a function of preserved depositional systems and systems tracts. Typically, the following architectural elements occur in ascending stratigraphic order: i) a basal unconformity, molded by fluvial incision and subaerial exposure during sea-level fall and shoreface erosion during subsequent rise; ii) a maximum regressive surface, which is coincident with the sequence boundary; iii) a transgressive systems tract including braided-river conglomerates and floodplain fines within the confines of an incised-valley, palustrine carbonates and back-barrier lagoon mudstones, and a deepening- and fining-upward shoreface to offshore-transition facies succession bounded at the base by a wave ravinement surface; iv) a sharp regressive surface of marine erosion produced by shoreface incision during relative sea-level fall; and v) a prograding, downstepping, and offlapping sharp-based lithofacies assemblage of either beach conglomerates or sandstones, ascribed to the falling stage systems tract, overlain by a rooted paleosol marking subaerial exposure. Sequences were deposited on the uplifting palaeo–Adriatic shelf in response to repeated high-frequency and high-amplitude eustatic changes in sea level that would promote the creation of accommodation space. By subtracting space to deposition, the contemporaneous regional uplift of the basin margin may be accounted for the shingled, downstepping configuration of individual sequences to form a falling stage sequence set of a larger composite sequence. In dip view, the erosional contact at the base of the Qm2 falling stage sequence set is a composite regressive surface, resulting from the downdip convergence and amalgamation of multiple erosional surfaces produced by the progressive basinward translation of successive sequences. Results from this study have direct implications for the oil and gas field development and exploration when making predictions of reservoir and seal geometries within shallow-marine, marginal-marine, and nonmarine sediments emplaced in similar long-term limited-accommodation settings. Highlights: Three high-frequency sequences developed in long-term limited-accommodation settings and their component nonmarine, marginal marine, and shallow-water facies associations are identified. Sequences consist of transgressive systems tracts (TST) and falling stage systems tracts (FSST). Transgressive sediments were deposited in incised fluvial valleys, back-barrier lagoons and nearshore to inner-shelf settings. Sharp-based forced regressive sediments were deposited within prograding sandy and gravelly beaches. The architectural framework provides a template for interpreting and predicting the distribution of a range of potentially viable reservoirs and source/sealing rocks.